Hydroxyethyl Starch Improves the Prognosis of Rats with Traumatic Shock via Activation of the ERK Signaling Pathway in Lymphocytes. (8th February 2022) - Liu, Yun; Lu, Jian; Dong, Caifu; Zhu, Limin; Zhou, Li; Zhu, Kai
Abstract : Objective . Severe traumatic shock is one of the leading causes of death in young adults. A large number of studies have shown that effective volumetry resuscitation on the basis of controlled injury can not only increase the success rate of early resuscitation but also reduce systemic inflammatory response and improve the cure rate of severe traumatic shock. The study explored the effects of hydroxyethyl starch (HES) on the survival rate, lymphocyte function and proliferation of rats with traumatic shock, and the potential mechanisms. Methods . Traumatic shock was constructed in rats as experimental model, and liquid resuscitation was performed using HES and lactated Ringer's (LR). 24-h mortality was recorded, and lymphocytes were isolated. The expressions of signaling pathway factors was detected by qPCR and Western blot. ELISA was performed to determine the expression of interleukin 6 (IL-6) and tumor necrosis factor- α (TNF- α ) in cell supernatant. Results . HES for fluid resuscitation augmented the survival of traumatic shock rats, upregulated the expressions of MEK and ERK1/2, and downregulated the expressions of IL-6 and TNF- α . However, inhibition of ERK signaling pathway reversed the effect of HES on the immune improvement and the 24-h survival rate of the traumatic shock rats (P < 0.05 ). Conclusion . HES could exert the anti-inflammatory effects on lymphocytes by mediating the phosphorylation of proteins of the ERK signaling pathway. HSE demonstrated a high efficacy in effectively treating traumatic shock, thus could be used in clinical practice.